Cultural values in Malay speech acts - Maros, Marlyna; Shaari, Azianura Hani (Universiti Utara Malaysia Press, 2019)
How do members of the new generation praise each other? Do they still adhere to the communication strategies prescribed in their traditional cultural values or modernization has played a role in initiating changes in people’s linguistic behavior?The book addresses the changes in the cultural values that have emerged in the speech acts of compliments and compliment responses of native speakers of Malay in Malaysia. In the field of sociolinguistics, the discussion provides insights into the current practices of the Malay speech acts and linguistic identity among the speakers, especially after 60 years of Malaysia’s independence. The rapid developments in technology and cyber communication have contributed to linguistic innovation and changes in language use to a certain extent, hence calling for a look at its impact on Malay cultural values.Through empirical evidence, the book attempts to elucidate the emerging norms that indicate changes in the cultural values of the new Malays. Our arguments are supported by the theories related to how utterances are analysed linguistically, taking into consideration the social factors, such as power, social distance, social status of the interlocutors and weight age of the imposition on the speech acts.This book is written to bring you closer to the members of the new generation, by providing insights into their strategies of communication. Specifically, it is written to uncover and understand the norms and values of the Malays of the 21st century.